A New Method for Assessment of Performing Mechanical Works of Energetic Compounds by the Cylinder Test. Issue 19 (22nd August 2016) - Fotouhi‐Far, Farshad; Bashiri, Hadis; Hamadanian, Masood; Keshavarz, Mohammad Hossein
Abstract: A new method is introduced for assessment of performing mechanical works of energetic compounds by cylinder wall velocities of CHNOFCl energetic compounds on the basis of the cylinder test. Four suitable decomposition paths are used to evaluate the number of moles of gaseous detonation products per gram of explosive, the average molecular weight of these gases, and the heat of detonation in calories per gram by considering different decomposition products HF, HCl, CO, N2, H2 O, H2, and CO2 . For CHNO and fluoro energetic compounds, the predicted cylinder wall velocities of these compounds give more reliable results than one of the best available empirical methods. The predicted root mean square (rms) deviations of cylinder wall velocities of the new model for some chloro explosives at actual radial expansions 0.6 and 1.9 mm are 0.010 and 0.062 km· s –1, which show high reliability of the new method. Abstract :